2022
DOI: 10.1039/d2ew00342b
|View full text |Cite
|
Sign up to set email alerts
|

A direct Z-scheme heterojunction g-C3N4/α-Fe2O3 nanocomposite for enhanced polymer-containing oilfield sewage degradation under visible light

Abstract: The massive discharge of polymer-containing sewage has caused more and more serious consequences to the production of the petroleum industry and the ecological environment. To solve the above problem, constructing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…In 2021, Zhu et al [73] successfully prepared a material (rGO@Fe 3 O 4 /Cu 2 O@ZnO) with strong hydrophobicity, high photocatalytic performance, and recyclability, and its photocatalytic degradation efficiency of acrylamide (AM) reached 97.3%. In addition to this, a large number of studies have reported the study of photocatalysts such as Cu 2 O [74,75], α-Fe 2 O 3 [76,77], Au [78], Ag [79], and Cu [80] for polymer degradation. Photocatalytic oxidation can utilize solar energy and save energy.…”
Section: Photocatalytic Oxidationmentioning
confidence: 99%
“…In 2021, Zhu et al [73] successfully prepared a material (rGO@Fe 3 O 4 /Cu 2 O@ZnO) with strong hydrophobicity, high photocatalytic performance, and recyclability, and its photocatalytic degradation efficiency of acrylamide (AM) reached 97.3%. In addition to this, a large number of studies have reported the study of photocatalysts such as Cu 2 O [74,75], α-Fe 2 O 3 [76,77], Au [78], Ag [79], and Cu [80] for polymer degradation. Photocatalytic oxidation can utilize solar energy and save energy.…”
Section: Photocatalytic Oxidationmentioning
confidence: 99%